2022
DOI: 10.3390/ijms23063214
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Family and Other Matrix Remodeling Proteins Identified by Bioinformatics Analysis as Hub Genes Involved in Gastric Cancer Progression and Prognosis

Abstract: Gastric cancer has remained in the top five cancers for over ten years, both in terms of incidence and mortality due to the shortage of biomarkers for disease follow-up and effective therapies. Aiming to fill this gap, we performed a bioinformatics assessment on our data and two additional GEO microarray profiles, followed by a deep analysis of the 40 differentially expressed genes identified. PPI network analysis and MCODE plug-in pointed out nine upregulated hub genes coding for proteins from the collagen fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 71 publications
2
14
0
Order By: Relevance
“…Even with the agreement that SPP1 was upregulated in GC, previous studies yielded conflicting observations regarding the prognostic role of SPP1 in GC. Several studies evaluating SPP1 expression from microarray data have suggested that there is no correlation between SPP1 expression in GC and the poor prognosis of patients [16,39]. In contrast, Bartolomeo et al showed that higher SPP1 expression was related to a poorer prognosis according to the IHC results of GC patients [15], which is consistent with our findings in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Even with the agreement that SPP1 was upregulated in GC, previous studies yielded conflicting observations regarding the prognostic role of SPP1 in GC. Several studies evaluating SPP1 expression from microarray data have suggested that there is no correlation between SPP1 expression in GC and the poor prognosis of patients [16,39]. In contrast, Bartolomeo et al showed that higher SPP1 expression was related to a poorer prognosis according to the IHC results of GC patients [15], which is consistent with our findings in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Growing evidence has demonstrated that patients with SPP1 overexpression have a poor prognosis in multiple cancers, including ovarian cancer [12], glioblastoma [13], and melanoma [14]. Regarding GC, however, the prognostic value of SPP1 remains controversial [15,16]. In addition, the expression level of SPP1 in macrophages was higher than that in cancer cells, and macrophage-derived SPP1 could upregulate downstream target genes, leading to tumor progression and drug resistance in cancer cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…COL12A1 is aberrantly upregulated in human malignancies including gastric cancer, colon cancer, colorectal cancer and pancreatic adenocarcinoma, and its upregulation correlated with tumor progression and poor prognosis [ 15 18 ]. Consistent with previous findings, the present research showed that COL12A1 is significantly upregulated in clinical iCCA relative to the nontumor liver tissues or HCC samples.…”
Section: Discussionmentioning
confidence: 99%
“…Significant advances in cancer biology were acquired in the last few years using bioinformatics analysis which highlighted deregulated genes and pathways involved in cancer development. Among the most frequently mentioned genes, the collagen family and other molecules of the tumor extracellular matrix always stood out and were associated with a poor prognosis in solid cancers [ 67 , 68 , 69 ].…”
Section: Collagen Family and Cancermentioning
confidence: 99%